Downlink radio resource management to enhance QoS of multimedia services in lte networks - Madi, Nadim K. M. (2018)
Long Term Evolution (LTE) has become the most dominant Fourth Generation (4G) mobile broadband network. The Radio Access Network (RAN) in LTE is designed to deliver a high trend of Quality of Service (QoS) over diverse user applications and several network scenarios. Therein, the functions of Radio Resource Management (RRM) features which span over the LTE protocol stack should be carefully developed to address related challenges, such as bandwidth utilization, resources scheduling, and physical channel’s power allocation. In upper level of downlink Medium Access Control (MAC) layer, the bandwidth distribution function is resided to manage the channel bandwidth over the offered user traffic to guarantee fair service. The performance of this function presents weaknesses when schemes such as Packet Prediction Mechanism (PPM) are adopted, hence the bandwidth is distributed in a linear and greedy fashion. Furthermore, flows scheduling with on-time transmissions is essential in Real-Time (RT) applications. PPM seems to guarantee a stable low delay for kinds of burst applications, other RT traffic are severely compromised though due to the aggressive data dropping procedures in high network overload states. From another aspect, recent QoS profiles count for energy-efficient transmissions as a core dimension. However, this aim still seeks a margin of enhancements with respect to the relevant power allocation schemes as seen in Piro and Lee schemes to focus on controlling the transmission power beside the system capacity maximization in order to maintain a long-term energy-efficient transmissions. This study figures out managing radio resources over different users for a particular purpose. The first proposal considers the issue of downlink channel resource distribution among different multimedia applications which lead to unfair service. Therefore, a "Frame-based Game Theory (FGT)" bandwidth distribution scheme is proposed for the MAC layer in the downlink LTE channel. In FGT, bandwidth is shared based on the data rate requirements of each traffic flow over the entire LTE frame. Simulation results reveal that FGT enhances the service fairness up to 25% with respect to the existing reference scheme and maintain a high data rate for different users. The second proposal considers the issue of flows scheduling for different RT flows. Therefore, Delay-based and QoS Aware Scheduling (DQAS) scheme is introduced to assign channel resources to delay sensitive flows based on QoS-derived rules for different flow types in a way to guarantee low latency and maintain a good data rate. Simulation results show that the efficient delay control in DQAS allows RT flows transmission with 55% minimum delay time compared to existing schemes and guarantees a reasonable throughput level for non-real time flows. Finally, the issue of surplus power allocation at the base station which degrades the system energy efficiency is discussed thoroughly. Accordingly, Link-adaptive Power Control and Allocation (LaPCA) scheme is proposed to tune the allowable power for the base station and adhere distributes this determined power among the utilized subchannels to transmit users’ data. The performance evaluation results indicate that LaPCA guarantees a high trend of energy-efficiency at the base station up to 23% with respect to existing works and keeps an outperforming level of network downlink transmissions. The findings of this study conceive several significant enhancements that are realized by the proposed RRM schemes. These enhancements include: a guaranteed fair bandwidth sharing among multi-traffic transmitted in unified LTE channel by introducing FGT scheme; stable and low delay for RT flows by introducing DQAS scheme; and finally, energy-efficient downlink transmissions with maximized system capacity by introducing LaPCA. Applying these proposed RRM-schemes in the current protocol stack of LTE radio access network persistently supports a high QoS level for communicating multimedia services in urban-like scenarios. Whereby, network utility and energy-efficient transmissions are significantly returned. This indeed allows more agility for network operators to define their QoS profiles which consequently maintain a long-term network service continuity within the kinds of highly dense environments.